THE ROLE OF CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE IN MITIGATING EARNINGS MANAGEMENT: EVIDENCE FROM INDONESIAN MANUFACTURING FIRMS - Harisriwijayanti Harisriwijayanti; Shinta Bella; Nike Apriyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the determinants of earnings management in the Indonesian manufacturing sector, focusing on the influence of independent commissioners, profitability, institutional ownership, and firm size. Using a quantitative approach and panel data regression analysis, the research examines financial data from manufacturing firms listed on the Indonesia Stock Exchange (IDX) between 2015 and 2019. The findings reveal that independent commissioners and institutional ownership significantly reduce earnings management, highlighting their roles as key governance mechanisms. Profitability, on the other hand, positively correlates with earnings manipulation, reflecting managerial pressures to sustain performance expectations. Firm size shows no significant effect, suggesting a complex balance between public scrutiny and managerial discretion. The results support agency theory by demonstrating the importance of effective monitoring in reducing opportunistic behavior. This study contributes to the literature on corporate governance in emerging markets and offers practical implications for policymakers, corporate leaders, and institutional investors to enhance financial transparency and accountability. Future research is encouraged to explore moderating factors and conduct cross-country comparisons for a more comprehensive understanding of earnings management practices.